Pelatihan Kewirausahaan Pembuatan Produk Olahan Pisang Bagi Mama-Mama Asli Papua di Kelurahan Mandala - Ferdinand Christianto Situmorang; Nurliah (Kawanad : Jurnal Pengabdian kepada Masyarakat, 2023)
The purpose of this service is to increase the entrepreneurial interest of Papua Aboriginal women in Mandala Village. We will also increase the production of banana raw materials that can be processed into products with high economic value. The method of delivery of this service activity is lecture, discussion, and hands-on practice. The outcome achieved was learning opportunities and support to improve entrepreneurial management, as well as entrepreneurial training on how to manufacture processed banana products for Papuan indigenous women in Mandala Village. In addition, increased interest in entrepreneurship among Papuan indigenous women in Mandala Village is expected to reduce unemployment and poverty in the region. This service activity is also expected to have a positive impact on the environment. B. Improve common interests and strengthen local economies. In the long term, this activity aims to be a role model for other communities to start businesses and develop local potential in their respective regions.